THE EFFECT OF “RICH MEDIA-GUIDED WRITING STRATEGY” ON STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT - Martina Handayani Silalahi; Sri Minda Murni (Universitas Negeri Medan, 2018)
This research aims at investigating the effect of rich media guided writing strategy on the students’ achievement in writing descriptive text. It was conducted by using experimental research design. The Population of this research was the tenth (X) grade students of SMA Negeri 1 Dolok Merawan. There were two classes as the sample. The first class (X MIA 1), the experimental group consisted of 20 students, and the second class (X IS 1), the control group consisted of 20 students. The experimental group was taught by using rich media-guided writing strategy while control group was taught by using pen and paper-guided writing strategy. The instrument for collecting the data was writing test. The data were analyzed by using t-test formula. The analysis showed that the score of students in the experimental group by using rich media guided writing strategy was higher than the score of students in the control group by using pen and paper guided writing strategy, at the level of significance (α) 0.05 with the degree of freedom (df) 38, the t-observed was 2,818 while the t-table was 2,024. Therefore, the application of rich media guided writing strategy significantly affected the students’ achievement in writing descriptive text. Keywords: Rich Media-Guided Writing Strategy, Writing Descriptive Text.